Nursing of 2 patients with rheumatoid arthritis treated with Huolong pot comprehensive moxibustion (火龙罐综合灸治疗类风湿关节炎2例护理体会) - HE Jing (何静); CHEN Hong (陈宏) (Association of Integrative Nursing, 2024)
This article summarizes the nursing practice of two patients with rheumatoid arthritis treated with Huolong pot comprehensive moxibustion. Based on the theory of syndrome differentiation and nursing of Traditional Chinese Medicine, comprehensive moxibustion treatment of Huolong por and the routine nursing measures such as dietary guidance, emotional nursing, daily life nursing, and health knowledge education were adopted to effectively relieve the clinical symptoms of pain and anxiety of patients. (本文总结2例类风湿关节炎患者行火龙罐综合灸治疗的效果观察及护理经验。基于中医辨证施护理论, 采取火龙罐综合灸治疗并配合饮食指导、情志护理、生活起居护理、健康知识宣教等常规护理措施, 有效改善患者疼痛、焦虑症状, 。)